"I'll work out tomorrow": The Procrastination in Exercise Scale. (November 2021) - Kelly, Scout M; Walton, Hayley R
Exercise procrastination (i.e. the voluntary delay of intended exercise) represents a novel, reasoned route to self-regulatory failure in physical activity. This study sought to develop and evaluate a scale to measure exercise procrastination and assess its relationship with self-reported physical activity. Two surveys were administered to community samples ( n  = 270, 279). In both samples, the Procrastination in Exercise Scale was positively correlated with general procrastination and predicted lower physical activity after controlling for intentions and general procrastination. Exercise procrastination appears to be a common phenomenon, and better understanding its role in physical activity may lead to novel intervention approaches.